Pengetahuan Ibu Tentang Hak ASI Anak dalam Perspektif Hukum dan Islam Sebagai Upaya Pencegahan Stunting - Septiana, Dewi; Kholis, Nur; Rahayu, Dewi (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2024)
This research discusses an analytical study of mothers' knowledge of children's breastfeeding rights from a legal and Islamic perspective as an effort to prevent stunting. Breastfeeding rights have been regulated in Government Regulation Number 33 of 2012 concerning Exclusive Breastfeeding in Article 6 “Every mother who gives birth must provide exclusive breastfeeding to the baby she gives birth to”. Although it has been regulated, the Basic Health Research data for 2021 shows that 52.5%, or only half of the 2.3 million babies aged less than six months receive exclusive breastfeeding in Indonesia. One of the impacts of children not getting breast milk is stunting. Data from 2020 shows that toddlers who are not exclusively breastfed are stunted by 91.7%. Stunting is a significant problem in Indonesia today; child malnutrition in the form of stunting, low body weight, and wasting continues to occur in children under five years of age. The large number of stunting that occur in toddlers who are not breastfed shows that there is still low awareness of mothers in providing breast milk even though the regulation of breastfeeding is very clear from legislation and Islamic law, there are still many mothers who do not offer breast milk to their children. Urgency of research Carry out research on children's rights to breast milk to prevent stunting. The research method that will be used in this research is empirical legal research using primary data and secondary data. The results showed that all respondents knew that breast milk is very beneficial for children and is taught in Islam, but only 42% knew that breast milk can prevent stunting. Despite knowing that breast milk is very helpful for children, 83% of respondents did not know that breast milk is a child's right that must be given. Mothers consider breastfeeding to be a mother's right, which means that mothers can choose whether or not to breastfeed their children. Breastfeeding as a child's right is not understood by the community, so many mothers ignore this right.